The design and implementation of an obstetric triage system for unscheduled pregnancy related attendances: a mixed methods evaluation - Sara Kenyon; Alistair Hewison; Sophie-Anna Dann; Jolene Easterbrook; Catherine Hamilton-Giachritsis; April Beckmann; Nina Johns (BMC, 2017)
Abstract Background No standardised system of triage exists in Maternity Care and local audit identified this to be problematic. We designed, implemented and evaluated an Obstetric Triage System in a large UK maternity unit. This includes a standard clinical triage assessment by a midwife, within 15 min of attendance, leading to assignment to a category of clinical urgency (on a 4-category scale). This guides timing of subsequent standardised immediate care for the eight most common reasons for attendance. A training programme was integral to the introduction. Methods A mixed methods evaluation was conducted. A structured audit of 994 sets of maternity notes before and after implementation identified the number of women seen within 15 min of attendance. Secondary measures reviewed included time to subsequent care and attendance. An inter-operator reliability study using scenarios was completed by midwives. A focus group and two questionnaire studies were undertaken to explore midwives' views of the system and to evaluate the training. In addition a national postal survey of practice in UK maternity units was undertaken in 2015. Results The structured audit of 974/992 (98%) of notes demonstrated an increase in the number of women seen within 15 min of attendance from 39% before implementation to 54% afterwards (RR (95% CI) 1.4 (1.2, 1.7) p = <0.0001). Excellent inter-operator reliability (ICC 0.961 (95% CI 0.91-0.99)) was demonstrated with breakdown showing consistently good rates. Thematic analysis of focus group data (n = 12) informed the development of the questionnaire which was sent to all appropriate midwives. The response rate was 53/79 (67%) and the midwives reported that the new system helped them manage the department and improved safety. The National Survey (response rate 85/135 [63%]) demonstrated wide variation in where women are seen and staffing models in place. The majority of units 69/85 (81%) did not use a triage system based on clinical assessment to prioritise care. Conclusions This obstetric triage system has excellent inter- operator reliability and appears to be a reliable way of assessing the clinical priority of women as well as improving organisation of the department. Our survey has demonstrated the widespread need for implementation of such a system.